Bioconversion of Sago Effluent to Organic Acids by Batch and Continuous Anaerobic Treatment with Pome Sludge as Inoculum - Ong, Ming Hooi (2001)
This study reports on the utilisation of the residual organics in sago starch processing effluent for the production of organic acids. Treatments were conducted under anaerobic conditions with mild mixing in batch and continuous operations. The production of organic acids was conducted at different concentrations of sludge (0%, 10%, 20% and 30%), pH (no pH adjustment, controlled constantly at pH 7, manual adjustment to pH 7 every 12 hours, initial pH 5.5 and pH 7) and retention time (5 days and 7.5 days). The conversion of residual starch to organic acids was very poor at only 1-2 g/L when the raw sago effluent was treated with its natural microflora and pH in batch system. However, when 20%-30% (w/w) of sludge was added, about 12- 13 g/L of organic acids were produced within 2 days of treatment, with lactic acid (9.5 g/L) and acetic acid (2.5 g/L) as the dominant acids, i.e. about 70% yield based on the initial COD of 18,000 mg/L. The results showed that treatment with intermittent pH adjustment at pH 7 every 12 hours with 20% of sludge addition appeared to give the highest organic acids concentration (13.4 g/L), with lactic, acetic and propionic acids at about 9.5 g/L, 2.5 g/L and 1.5 g/L respectively. The acid composition was dependent on the pH. Acetic acid was mainly produced at neutral pH range with more than 60% selectivity and lactic acid at lower pH range. At pH 5.5, lactic acid remained in the medium much longer and a higher selectivity of more than 80% could be achieved. During the continuous anaerobic treatment with 5 days retention time, about 7-8 g/L of organic acids was attained under the steady state condition. By increasing the retention time to 7.5 days, total organic acids ranged from 6-6.5 g/L was obtained during the steady state with total microbial population stabilized at 107 cfu/mL in the reactor. The continuous treatment system succeeded to remove the suspended solids of the effluent which mainly comprised of residual starch from 18000 mg/L to 2000 mgIL during the steady state. This represented more than 80% of suspended solids removal. The suspended solids which contributed to the COD of the effluent was converted to organic acids with 45% yield at steady state. After the recovery process by ion-exchange chromatography and evaporation, 7.5 and 8.2 times of organic acids concentration could be achieved with the final concentration attained at 52.3 g/L and 61.3 g/L respectively. The recovery system was capable of removing more than 80% COD from the sago effluent.